KEWENANGAN PENANGANAN PEMBAJAKAN DAN PEROMPAKAN DI LAUT YURIDIKSI NASIONAL OLEH TNI ANGKATAN LAUT PASCA LAHIRNYA UU RI NOMOR 34 TAHUN 2004 TENTANG TNI - Pawana, Juang; Rai Djaja, Ida Bagus (Kertha Negara : Journal Ilmu Hukum, 2013)
In writing scientific work called “ The authority handling piracy and piratical at sea jurisdiction national by the navy after it birth of Law RI no 34 / 2004 about TNI. The author uses the normative research methods. In article 4, paragraph 1 of Law RI no 34/2004 that TNI consisting of the army, the navy and air forces conducting its function in matra or combined under the panglima. Article 7 paragraph 2 ( 14 ) of Law RI no 34/2004 to base TNI to help the government in securing the cruise and atc against piracy, piratical and smuggling. Article 7 paragraph 2 ( 14 ) of Law RI no 34/2004 must be implemented based on policy and a political decision state corresponding article 7 paragraph 3 of Law RI no 34/2004. While in article 9 ( b ) of Law RI no 34/2004 was legal basis from duty the navy in enforcing laws and increase the security in the region of the jurisdiction national according the legal national and international laws that have ratified. One of international law was the 1982 UNCLOS has been ratified in Law DECREE No. 17 of 1985. Differences in understanding exist amongst the community in addressing piracy and piracy in the seas of the national jurisdiction of the Indonesian Navy had done directly without any State policies and political decisions.
Keywords: UNCLOS 1982, The national jurisdiction of the sea, Piracy and Sea Robbery